Making it on Civvy Street: An Online Survey of Canadian Veterans in Transition - Black, Timothy; Papile, Chiara (Canadian Journal of Counselling and Psychotherapy, 2010)
The authors present the results of a non-governmental study focusing on Canadian Forces veterans and their experiences of transition from the military into civilian society. The study was based on a survey that gathered basic demographic data and veterans’ subjective experiences of their transition out of the Canadian military into civilian life. These experiences included: the difficulty of the transition, help-seeking behaviours, issues struggled with upon release, and perceived appreciation by Canadian society for their role in the CF. Results are discussed with respect to societal implications, interventions, the role of counsellors in working with veterans, and future research.